Tribologically induced crystal rotation kinematics revealed by electron backscatter diffraction. (15th February 2022) - Haug, C.; Molodov, D.; Gumbsch, P.; Greiner, C.
Abstract: Tribological loading of metals induces microstructural changes by dislocation-mediated plastic deformation. During continued sliding, combined shear and lattice rotation result in the formation of crystallographic textures which influence friction and wear at the sliding interface. In order to elucidate the fundamental lattice rotation kinematics involved in this process during the early stages of sliding, we conducted unlubricated, linear single pass sliding experiments on a copper bicrystal using sapphire spheres. Electron backscatter diffraction (EBSD) performed directly on the bulk surface of the wear tracks in the vicinity of the grain boundary reveals crystal lattice rotations by approximately up to 35°. Predominantly, the tribologically induced crystal rotations appear to be kinematically constrained to rotations around the transverse direction (TD) and occur in both grains, irrespective of load (2 to 8 N). We demonstrate that inverting the sliding direction (SD) inverts the sense of crystal rotation, but does not change the principal nature of rotation for the majority of indexed EBSD data. A lower proportion of the crystal lattice rotates much farther around TD (roughly up to 90°), accompanied by a superimposed crystal rotation around ±SD. Analysis reveals that sliding direction and grain orientation exert a systematic influence of how crystal rotations are accommodated. This is rationalized in terms of geometry, anisotropic wear track profiles and slip traces. Under specific conditions, combined crystal rotation and twinning are observed. These detailed insights into the fundamental nature of tribologically induced lattice rotation kinematics provide important guidance for applied research targeting materials with superior tribological properties. Graphical abstract: Image, graphical abstract